PENINGKATAN HASIL BELAJAR SISWA MELALUI MODEL KOOPERATIF DENGAN PENDEKATAN TIPE NUMBERED HEADS TOGETHER - Tulus Wijayanto; Dwi Sugeng Winarto (saintifika, 2021)
In teaching and learning activities, students who are active in the learning process will gain learning experiences that will affect student learning outcomes. When the teacher only uses the lecture method in delivering material, students will tend to listen and not be actively involved in teaching and learning activities. This research is a classroom action research consisting of two cycles with different materials, each cycle consisting of four stages, namely: planning, action, observation and reflection. The population in this study were all students of class VIII B of SMPN 7 Jember in the 2019/2020 lesson, totaling 32 students. Learning outcome data is in the form of psychomoric learning outcomes in the form of mental activities and student affective learning outcomes obtained from observation sheets during the teaching process, and cognitive learning outcome data is obtained from evaluation tests. The results showed that from the two cycles taken, data was obtained that the completeness of the students' classical mental learning outcomes was 73.50% in the first cycle and 89.00% in the second cycle, respectively. Classical mastery of cognitive learning outcomes 72.10% in cycle I and 88.90% in cycle II. While the classical completeness of affective learning outcomes was 78.40% in the first cycle and 90.30% in the second cycle.